From bildungsroman to geschäftsroman: the posthuman neoliberal novel - AlAmmouri, Bayan; Salman, Dina (Penerbit Universiti Kebangsaan Malaysia, 2021)
The emergence of posthumanism and the proliferation of neoliberal rationality have not only changed the meaning of the word human, but also the status of the human. Technological autonomy overpowers and replaces human agency and the human becomes marginal and peripheral on a planetary scale; in the same manner that humans have lost control over the machine, they have also lost control over their agentic narrative on a global scale and on a literary one. And in the same way neoliberal commodification reduces humans to non-humans and transforms technology to a transcendent other that can transform and control the body, neoliberal posthumanism transformed the genre of the novel. The authors argue that the decentralization of the human, triggered by posthumanism, and the commodification of the genre of the novel, triggered by neoliberalism, transformed the most popular subgenre of the novel, the bildungsroman into a geschäftsroman. There is considerable evidence that indicates that many contemporary novels no longer focus on the growth of human beings, but rather on the growth of businesses, instead. This paper analyzes Mohsin Hamid’s How to get Filthy Rich in Rising Asia (2013), arguing that it is a poignant example of a geschäftsroman, in which the human is decentralized and the growth of the city and the development of the economy become the narrative’s nucleus.